Pengaruh Good Corporate Governace (GCG) Terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia - Fitriya Sari; Rinni Indriyani; Michael Fanji Suyatno (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the influence of Good Corporate Governance (GCG) on the Financial Performance of Sharia Commercial Banks (2018-2022 Period). This study used a quantitative type of research. The data used in this study is secondary data, because the data is obtained from documents by browsing the official website of the Annual Report of Islamic commercial banks published on the website of each Company. In this study, the independent variables are Managerial Ownership (X1), Institutional Ownership (X2), Independent Board of Commissioners (X3) and Audit Committee (X4). The population of this study is all Sharia Commercial Banks registered with the Financial Services Authority for the period 2018-2022 consisting of sixteen companies. Researchers sampling using Purposive Sampling techniques. The data analysis technique used in this study is path analysis with the help of SPSS applications. The results of data analysis show that managerial ownership has no partial effect on financial performance. Institutional Ownership has no partial effect on Financial Performance. The independent board of commissioners partially influences Financial Performance. The audit committee has no partial effect on Financial Performance. Companies should always strive to maintain good corporate governance